Current Advances and Future Perspectives of Advanced Polymer Processing for Bone and Tissue Engineering: Morphological Control and Applications - Zhang, Tongrui; Nie, Min; Li, Yijun (Frontiers in Bioengineering and Biotechnology, 2022)
Advanced polymer processing has received extensive attention due to its unique control of complex force fields and customizability, and has been widely applied in various fields, especially in preparation of functional devices for bioengineering and biotechnology. This review aims to provide an overview of various advanced polymer processing techniques including rotation extrusion, electrospinning, micro injection molding, 3D printing and their recent progresses in the field of cell proliferation, bone repair, and artificial blood vessels. This review dose not only attempts to provide a comprehensive understanding of advanced polymer processing, but also aims to guide for design and fabrication of next-generation device for biomedical engineering.